Java : a beginner's guide - Schildt, Herbert (San Francisco, CA : McGraw-Hill Osborne Media, 2011)
'Essential Java programming skills made easyFrom Herb Schildt, the number-one programming author worldwide, comes this fully revised and updated introductory Java guide. You will get all the information you need to get up and running with the latest version of the most popular Web programming language. Java: A Beginner's Guide, Fifth Edition will have you programming in Java right away. The book has been updated to cover the new features of Java including closures, the enhanced switch statement, the enhanced catch statement, and extension methods, and more. Designed for Easy Learning: Key Skills & Concepts--Chapter-opening lists of specific skills covered in the chapter Ask the Expert--Q & A sections filled with bonus information and helpful tips Try This--Hands-on exercises that show you how to apply your skills Notes--Extra information related to the topic being covered Tips--Helpful reminders or alternate ways of doing things Self Tests--End-of-chapter reviews to test your knowledge Annotated syntax--Example code with commentary that describes the programming techniques being illustrated Full coverage of Java essentials: Java Fundamentals; Introducing Data Types and Operators; Program Control Statements; Introducing Classes, Objects, and Methods; More Data Types and Operators; A Closer Look at Methods and Classes; Inheritance; Packages and Interfaces; Exception Handling; Using I/O; Multithreaded Programming; Enumerations, Autoboxing, and Static Import; Generics; Applets, Events, and Miscellaneous Topics; Introducing Swing'--
'Fully updated to cover Java Platform, Standard Edition 7 (Java SE 7), Javaʼ: A Beginner's Guide, Fifth Edition starts with the basics, such as how to compile and run a Java program, then discusses the keywords, syntax, and constructs that form the core of the Java language. You'll also find coverage of some of Java's most advanced features, including multithreaded programming and generics. An introduction to Swing concludes the book. Get started programming in Java right away with help from this fast-paced tutorial'--
Buku bacaan asas fakulti
Keywords: Java (Computer program language); COMPUTERS / Programming Languages / Java